„Pamiątka z bratania się...” Fotograficzna dokumentacja fenomenu fraternizacji na froncie wschodnim I wojny światowej w 1917/18 roku - Mieczkowski, Rafał (Klio - Czasopismo Poświęcone Dziejom Polski i Powszechnym, 2022)
In year 1917 the Russian war effort was heavily affected by the outbreak of the revolution(s) and the events that followed. Having lost faith in their own commanders, the common Russian soldier has become especially vulnerable to anti-war propaganda. Thus the spontaneous cases of ceasefire and peaceful meetings with enemy soldiers on no man’s land have become common, Such events were frequently documented by photographers present on site, and their works allows us to take a better, almost first-hand look at these unusual wartime activities. The double perspective of such images (propaganda- and commemorative one) allows us to take an unique view on the last stage of the Great War on East.